MANHAJ AL IQTISHOD NAHDLATUL ULAMA’; The Construction of Ahl alSunnah Wa al-Jamā'ah Paradigm in Global Economic Contestation - Mashur Imam (International Conference on Humanity Education and Society (ICHES), 2023)
The discourse on global economic contestation originates from the conflict between socialism and capitalism. Socialism Socialism approves of state intervention in the market and breeds discrimination of people's economic rights. Meanwhile, capitalism believes in extreme market freedoms and undermines the state power in its pursuit of economic justice. Both of them proved unable to face the crisis. Nahdaltul Ulama' (NU) as the largest organization in Indonesia, seeks to play a role in the global economic contestation. This article reveals how NU Paradigm in the midst of global economic contestation? How is the construction of manhaj al Iqtishad in facing with crisis that caused by economic contestation?. This research is a literature review. These two important questions are detailed using a historical document analysis approach regarding NU's role in economic contestation. The analysis is carried out by connecting the findings with the reasoning contestation that occurs. The finding conclusion is the construction of Manhaj ahl al-sunnah wa al-jamā'ah as manhaj al Iqtishad in the midst of global economic contestation.